2018
DOI: 10.1007/s10803-018-3545-6
|View full text |Cite
|
Sign up to set email alerts
|

Parent Expectations and Preparatory Activities as Adolescents with ASD Transition to Adulthood

Abstract: Community stakeholders, researchers, and providers are increasingly focused on individual, family, and systemic factors that contribute to positive outcomes for adults on the autism spectrum. Parent expectations for their youth's future are associated with adult outcomes (e.g., employment, school success, independence), yet the mechanism for this effect remains unclear. This study investigated how expectations were related to parent transition-related activities in a sample of 298 parents of adolescents on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
28
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 47 publications
4
28
0
Order By: Relevance
“…The expectancy–value theory of achievement motivation (Eccles & Wigfield, 2002) links expectations and decision-making, which provides theoretical support for our hypothesis. The research our team has published since conducting this study also lends additional support to this hypothesis, wherein, we identified parent expectations as significant predictors of transition preparation activities in a sample of 298 parents of youth with ASD (Holmes et al, 2018). Specifically, we found that financial independence expectations predicted talking about jobs, and independent living expectations predicted assigning chores and enrollment in adult skills classes (Holmes et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…The expectancy–value theory of achievement motivation (Eccles & Wigfield, 2002) links expectations and decision-making, which provides theoretical support for our hypothesis. The research our team has published since conducting this study also lends additional support to this hypothesis, wherein, we identified parent expectations as significant predictors of transition preparation activities in a sample of 298 parents of youth with ASD (Holmes et al, 2018). Specifically, we found that financial independence expectations predicted talking about jobs, and independent living expectations predicted assigning chores and enrollment in adult skills classes (Holmes et al, 2018).…”
Section: Discussionsupporting
confidence: 54%
“…For example, Kirby (2016) identified parent expectations for autistic youth as a significant mediator of transition outcomes. Evidence suggests that parents with higher expectations raise autistic youth who engage in more transition preparation activities (Holmes et al, 2018) and ultimately achieve more independent outcomes in adulthood (Kirby, 2016). Thus, it is important to understand parent perspectives and consider how they can best support the transition process to promote better outcomes for autistic adults.…”
Section: Introduction and Literature Reviewmentioning
confidence: 99%
“…Kirby's finding highlights the importance of further exploring parental expectations; the association between parental expectations and youth's outcomes appears complex. To explore the relationship between parents' expectations and youth's outcomes, Holmes, Kirby, Strassberg, and Himle (2018) conducted a study regarding potential predictors of parents' expectations for their autistic adolescent's adult life, as well as whether parents' expectations predicted the family's engagement in certain transition preparation activities. Their findings suggest that youth factors such as ASD severity, IQ, and gender could predict parents' expectations.…”
mentioning
confidence: 99%